Contextual Adaptation of the Unified Protocol for the Transdiagnostic Treatment of Emotional Disorders in Victims of the Armed Conflict in Colombia: A Case Study. Issue 2 (May 2019) - Castro-Camacho, Leonidas; Moreno, Julián David; Naismith, Iona
Abstract: The delivery of a contextually adapted version of the Unified Protocol for transdiagnostic treatment of emotional disorders is illustrated through a case study of an internally displaced female victim of armed conflict in Colombia. A detailed account of how her history of continuous traumatic events and her forced displacement resulted in multiple emotional disorders and behaviors which hindered her ability to react to daily stressors illustrates the particular conditions of individuals exposed to extreme violence. Emphasis is placed on how her culture and context required adaptations of evidence-based interventions. The contextually adapted UP (CXA-UP) is described in "slow-motion, " through a session-by-session account of the procedure along with the specific changes in each module. Outcome measures showed four positive diagnoses at pretreatment, but none at posttreatment, 3-month, or 2-year follow-up. Implications for global applications with individuals in similar contexts and for widening access to such interventions are discussed.